Cytokine Immunopathogenesis of Enterovirus 71 Brain Stem Encephalitis - Shih-Min Wang; Huan-Yao Lei; Ching-Chuan Liu (Clinical and Developmental Immunology)
Enterovirus 71 (EV71) is one of the most important causes of herpangina and hand, foot, and mouth disease. It can also cause severe complications of the central nervous system (CNS). Brain stem encephalitis with pulmonary edema is the severe complication that can lead to death. EV71 replicates in leukocytes, endothelial cells, and dendritic cells resulting in the production of immune and inflammatory mediators that shape innate and acquired immune responses and the complications of disease. Cytokines, as a part of innate immunity, favor the development of antiviral and Th1 immune responses. Cytokines and chemokines play an important role in the pathogenesis EV71 brain stem encephalitis. Both the CNS and the systemic inflammatory responses to infection play important, but distinctly different, roles in the pathogenesis of EV71 pulmonary edema. Administration of intravenous immunoglobulin and milrinone, a phosphodiesterase inhibitor, has been shown to modulate inflammation, to reduce sympathetic overactivity, and to improve survival in patients with EV71 autonomic nervous system dysregulation and pulmonary edema.